The effects of dub-off angle on chip evacuation in single-lip deep hole gun drilling - Wan, S. (2016)
Without proper chip evacuation, gun drills will fail under intense thermal and mechanical loading during deep hole drilling of high temperature superalloys like Inconel 718. In gundrilling, the efficiency in evacuating chips is governed by the geometry of gun drills that defines the hydraulic boundary conditions for coolant and chip flow. In this paper, we propose a novel computational fluid dynamics (CFD) model that is capable to simulate and quantify the chip transportation behavior under high pressure coolant for drill geometry optimization. This is demonstrated through a case study on improving the shoulder dub-off design of commercial gun drills, which have a high tendency in trapping chips at the hole bottom. A more effective design criterion for the shoulder dub-off is thus proposed.